2019
DOI: 10.1186/s12880-019-0314-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of magnetic resonance imaging combined with gene analysis for the diagnosis of fetal congenital heart disease

Abstract: BackgroundFetal deformity is a disease caused by abnormal chromosome structure, which may be influenced by genetic factors as well as the maternal and external environment. Magnetic resonance imaging (MRI) may be used to effectively diagnose fetus deformities. However it has been reported that gene analysis is a more accurate diagnostic method. The aim of the present study was to investigate the effectiveness of MRI in combination with gene analysis for the diagnosis of fetal congenital heart disease, a form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A recent research study showed that magnetic resonance imaging, in combination with gene analysis using array comparative genome hybridization analysis and fluorescence in situ hybridization could be a more effective diagnostic method for CDHs [ 149 ]. Similarly, molecular biomarkers too have shown considerable promise for use in prenatal diagnosis of CHD [ 150 , 151 , 152 ].…”
Section: Diagnosis Of Chdmentioning
confidence: 99%
“…A recent research study showed that magnetic resonance imaging, in combination with gene analysis using array comparative genome hybridization analysis and fluorescence in situ hybridization could be a more effective diagnostic method for CDHs [ 149 ]. Similarly, molecular biomarkers too have shown considerable promise for use in prenatal diagnosis of CHD [ 150 , 151 , 152 ].…”
Section: Diagnosis Of Chdmentioning
confidence: 99%
“…The magnetic resonance imaging (MRI) is considered one of the noninvasive imaging methods in radiology for diagnosis to detect the soft organs size, shape and homogeneity [9]. MRI safety and quality of imaging was confirmed in diagnosis of the pediatric and adult patients with congenital heart disease [10], and oncology diagnosis [11] in different types of cancer: for examples, breast cancer [12], cervical cancer [13], lung cancer [14] and prostate cancer [15]. Using MRI during the experimental trial on animal models supports the researchers with all data about localization or metastasis of cancer whether about the solid or ascites tumor.…”
Section: Introductionmentioning
confidence: 99%